Stellar systems in the direction of the Hickson Compact Group 44 : I. Low surface brightness galaxies - Smith Castelli, Analía Viviana (2016)
Context. In spite of the numerous studies of low-luminosity galaxies in different environments, there is still no consensus about their formation scenario. In particular, a large number of galaxies displaying extremely low-surface brightnesses have been detected in the last year, and the nature of these objects is under discussion. Aims. In this paper we report the detection of two extended low-surface brightness (LSB) objects (μeffg′ ≃ 27 mag) found, in projection, next to NGC 3193 and in the zone of the Hickson Compact Group (HCG) 44, respectively. Methods. We analyzed deep, high-quality, GEMINI-GMOS images with ELLIPSE within IRAF in order to obtain their brightness profiles and structural parameters. We also searched for the presence of globular clusters (GC) in these fields. Results. We have found that, if these LSB galaxies were at the distances of NGC 3193 and HCG 44, they would show sizes and luminosities similar to those of the ultra-diffuse galaxies (UDGs) found in the Coma cluster and other associations. In that case, their sizes would be rather larger than those displayed by the Local Group dwarf spheroidal (dSph) galaxies. We have detected a few unresolved sources in the sky zone occupied by these galaxies showing colors and brightnesses typical of blue globular clusters. Conclusions. From the comparison of the properties of the galaxies presented in this work with those of similar objects reported in the literature, we have found that LSB galaxies display sizes covering a quite extended continous range (reff ∼ 0.3-4.5 kpc), in contrast to "normal" early-type galaxies, which show reff ∼ 1.0 kpc with a low dispersion. This fact might point to different formation processes for both types of galaxies.